1982
DOI: 10.1152/ajprenal.1982.242.4.f340
|View full text |Cite
|
Sign up to set email alerts
|

Potential-dependent D-glucose uptake by renal brush border membrane vesicles in the absence of sodium

Abstract: The uptake of D-glucose by renal brush border membrane vesicles was studied in the absence of Na+. Uptake of the sugar was membrane potential dependent (inside negative), inhibited by phlorizin, sugar and stereospecific, accelerated by exchange diffusion, saturable, and temperature dependent. The binding of phlorizin in the absence of Na+ was also increased by a membrane potential (inside negative). Thus, the properties of this membrane potential-dependent, Na+-independent sugar transport system resembled thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…(For a discussion of the quantitative differences between these two transport systems, see Toggenburger et al, 1982.) Also a recent, independent observation of Hilden and Sacktor (1982) on the kidney cotransporter(s) fits beautifully in the mechanistic model of Fig. 9.…”
Section: A Plausible Mechanistic Modelsupporting
confidence: 60%
See 2 more Smart Citations
“…(For a discussion of the quantitative differences between these two transport systems, see Toggenburger et al, 1982.) Also a recent, independent observation of Hilden and Sacktor (1982) on the kidney cotransporter(s) fits beautifully in the mechanistic model of Fig. 9.…”
Section: A Plausible Mechanistic Modelsupporting
confidence: 60%
“…(v) Finally, A0 (negative inside) accelerates D-glucose influx into and increases phlorizin binding onto the (renal) brush border cotransporter even in the absence of Na + (Hilden & Sacktor, 1982). Phlorizin binds to the (intestinal) cotransporter in the neutral form (Toggenburger et al, 1978) and, of course, so does D-glucose.…”
Section: The "Gate" Bearsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to these problems, the role of H+ in usual Nat-dependent cotransport system, particularly under Na+-free conditions is of special interest. HILDEN and SACKTOR [28] demonstrated that D-glucose transport across renal brush border membrane vesicles in the absence of Na+ was stimulated by inside-negative K+ diffusion potential though the mechanism of stimulation was unknown. Interestingly, it was observed that Na+-independent d cp m-stimulated D-glucose transport across the same membranes was dependent on the pH gradient (Takuwa and Hoshi, unpublished observation).…”
Section: Other W-dependent Transport Processes In Animal Cell Membranesmentioning
confidence: 99%
“…With the aid of membrane vesicle preparations in which the microenvironment -and thus the reservoirsurrounding the brush-border membrane in intact tissue has been destroyed, it has been shown that the mediated uptake of sugars and amino acids is strongly dependent on the presence of sodium ions (Murer & Hopfer, 1974). Although widely accepted, even this doctrine has however recently been questioned (Hilden & Sacktor, 1982). An absolute dependence on sodium would imply that only the ternary complex (SCA in Fig.…”
Section: Discussionmentioning
confidence: 99%